Robust MISO downlink precoder design with per-antenna power constraints - Medra, Mostafa; Davidson, Timothy N. (SPAWC : signal processing advances in wireless communications, 2015)
We consider the design of a linear precoder for a multiple-input single-output (MISO) downlink system that seeks to mitigate the impact of the imperfections in the channel state information (CSI) that is available at the base station (BS). The goal of the design is to minimize the outage probability of signal-to-interference-and-noise ratio (SINR) targets specified by the receivers, while satisfying constraints on the power transmitted by each antenna and a total transmitted power constraint. The proposed algorithm exploits a recently developed broadly applicable approximation of the outage probability. That approximation results in a problem formulation that can be efficiently solved by adapting existing low-computational-cost algorithms for scenarios with perfect CSI and per-antenna power constraints. Simulation results show that robust designs with a uniform and near-uniform power distributions across the transmitting antennas can be obtained without a substantial degradation in the outage probability.